(untitled) (Defense and Security Studies, 2023)
Migrations, which are as old as the history of mankind, have taken place for many reasons and have increased with the addition of new ones. Although wars and economic concerns are among the main causes, environmental problems have been one of the reasons that should be accepted in today’s world. Environmental problems that threaten the lives of all living beings, especially human beings, pose numerous risks. Moreover, these risks have reached unlimited and global dimensions. One of these risks is the forced migration of people due to various environmental problems, especially climate change. Those who have experienced this migration are defined as "environmental refugees", and they occupy an important place in recent literature. While many of the problems associated with the millions of migrants are still unresolved today, the fact that environmental refugees are being added with increasing momentum clearly demonstrates the importance of including this issue in research agendas. It is also a fact that migration poses serious problems not only for the migrants who are its subjects but also for the countries of emigration. The importance of the subject from both sides and the fact that it is pregnant with many problems, which can be seen with the domino effect, made it necessary to study the subject in detail. Based on these considerations, in the study; the history of environmental refugees, its causes, problems, environmental refugees mobility in recent years, possible future scenarios, and social-economic dimensions are discussed, as well as evaluation and solutions are given.